Composite Modification of Water Hyacinth Fiber in the Production of Decorative Particle Boards by Spray-Coating Utilizing a Silane Coupling Agent - Syahputra, Romi Fadli; Sasmita, Sasmita; Ginting, Delovita (LPPM Universitas Muhammadiyah Riau, 2024)
Water hyacinth is a waste in waters that can damage the balance of aquatic ecosystems because of its rapid growth, which can reach 3% in a day. One utilization of water hyacinth waste is to be used as filler material for decorative particleboard. This study aims to look at the physical and mechanical characteristics of particleboard with surface coating treatment using silane coupling agent solution.. Water hyacinth fiber was selected as an alternative filler material for the particle board composite due to its abundant availability and potential fiber properties. The surface of the particle boards was modified using a silane coupling agent (KH550) to enhance the bond quality between components. The water hyacinth powder was first alkalized with NaOH and distilled water (1:5) for 1 hour, then mixed with epoxy resin in a 40:60 weight ratio. The compaction process was carried out using a hydraulic hot press at 2 bar pressure and 50°C temperature for 10 minutes. The resulting particle boards were tested for density, moisture content, water absorption, and thickness swelling. Flexural testing was conducted in accordance with ASTM D790-03, and tensile strength testing followed ASTM D638-14. Surface morphology was observed using a scanning electron microscope (SEM). The results showed that the application of a silane coupling agent improved the bond between the matrix and filler, and the produced particle boards met the quality standards for density, moisture content, water absorption, thickness swelling, flexural strength, and tensile strength.